The Interference of Soil Bacteria by Quorum Sensing Inhibitory Activity with the Biofilm of Pathogenic Pseudomonas aeruginosa Isolates - Abdul Hussain, Samer Raad; Lafta, Inam Jasim (Iraqi Journal of Science, 2026)
Pseudomonas aeruginosa’s biofilm may have a role in its resistance to antibiotics. By interfering with the quorum sensing (QS) system, biofilm formation in pathogens may be inhibited, thereby reducing resistance to antibiotics. Therefore, new approaches for treating bacterial infections could be offered by applying QS inhibitors (QSIs). Recently, soil microorganisms have been employed as they created compounds with QS inhibition properties. Thus, the current study aimed to examine the ability of facultatively anaerobic soil bacteria to impede the QS of P. aeruginosa, thereby interfering with QS-regulated biofilm production. In this research, the soil bacteria were isolated and identified by the Vitek2 system. The soil isolates included five Proteus mirabilis, two Klebsiella pneumoniae subsp. pneumoniae, and one isolate of each Staphylococcus aureus and Escherichia coli. These isolates were tested for their ability as potential QS inhibitors (QSIs). Then, the whole cell crude aqueous and organic extracts of a P. mirabilis soil isolate were made, and their minimum inhibitory concentration (MIC) and sub-MIC were determined against eight clinical P. aeruginosa isolates. The clinical bacteria involved four isolated from burn wound infections and the other four from cystic fibrosis patients. The crude aqueous extract was then tested as an anti-biofilm interfering with P. aeruginosa using the crystal violet assay and by the use of quantitative real-time polymerase chain reaction (qPCR) targeting the LasI gene, the QS regulator. The results showed that the P. mirabilis aqueous extract effectively weakened the P. aeruginosa biofilm and reduced the expression of the QS regulatory LasI gene. To conclude, P. mirabilis revealed a promising result in the QS inhibition, and its crude extract successfully rendered the strong biofilm producers P. aeruginosa weaker.